Cyclopolymerization of Divinylmonomer with A Novel Redox Pair of Mn(VII)-Tetramethylethylenediamine - Umayavalli, M.; Krishnaveni, N.; Sivakumar, G. (Asian Journal of Chemistry, 2012)
Kinetics of cyclopolymerization of N,N'-methylenebisacrylamide (MBA) was studied with a novel redox pair of Mn(VII)-tetramethylethylenedi- amine in a homogeneous gel free state under varying conditions of concentration, temperature, ionic strength and pH. Polymerization of N,N'-methylenebisacrylamide was carried out in acid medium at low concentrations with Mn(VII)-tetramethylethylenediamine as redox initiator at 50 ºC. The dependence of the rate of polymerization various experimental conditions, such as different concentrations of monomer, Mn(VII), tetramethylethylenediamine and different ionic strength at different temperature were studied. The rate of polymerization was found to be independent of ionic strength and pH. The rate of polymerization showed an increase with increase in temperature. The rate of polymerization was found to depend on [monomer]1 and independent of [Mn(VII)] and [tetramethylethylenediamine] over a range. A polymerization mechanism involving cyclopolymerization mechanism was addressed. Evaluation of composite rate constant is in good agreement with the suggested mechanism. Under steady state conditions the rate of cyclo-polymerization is: Rp = kpkd/kt × MBA.